2002
DOI: 10.1002/ajmg.10199
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in familial dominant Paget disease of bone and muscular dystrophy

Abstract: The combination of autosomal dominant, early onset Paget disease of bone (PDB) and muscular dystrophy is an unusual disorder. We recently mapped the disorder in a large family from central Illinois with PDB and proximal limb-girdle type of muscular dystrophy (LGMD), and in 3 additional families with hereditary inclusion body myopathy (HIBM), Paget disease of bone and frontotemporal dementia, to a unique locus on chromosome 9p21.1-q12. The present study describes an unrelated 10-member family with autosomal dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…Waggoner et al reported familial myopathy with distal distribution of weakness, diaphyseal location of the bone changes, no rimmed vacuoles on muscle biopsy and no link to the VCP gene locus [12]. The family reported by Metha et al disclosed no rimmed vacuoles and no inclusion bodies in the muscle biopsy, fractures of the diaphyseal part of the bone early in life and no mutation in the VCP gene [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waggoner et al reported familial myopathy with distal distribution of weakness, diaphyseal location of the bone changes, no rimmed vacuoles on muscle biopsy and no link to the VCP gene locus [12]. The family reported by Metha et al disclosed no rimmed vacuoles and no inclusion bodies in the muscle biopsy, fractures of the diaphyseal part of the bone early in life and no mutation in the VCP gene [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to the families with VCP gene mutations, the combination of familial Paget's disease of bone with myopathy has been previously reported in only one family unlinked to the VCP gene locus and three other unrelated families with distinct phenotypes [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…VCP mutations are not the only genetic cause of a multisystem degenerative phenotype encompassing muscle, brain and bone (Waggoner et al, 2002;Kottlors et al, 2010). For example, mutations in two paralogous RNA-binding proteins, hnRNPA1 and hnRNPA2B1 were found to cause a clinically indistinguishable syndrome but without VCP mutations (Kim et al, 2013a).…”
Section: Box 2 Clinical Syndromes Associated With Vcp Mutationsmentioning
confidence: 99%
“…Mutations in the valosin-containing protein (VCP) gene were the first identified cause of IBMPFD, 1,2 but reports of families without linkage to chromosome 9 established the genetic heterogeneity of the disorder. 3,4 It has recently emerged that mutations in the HNRNPA2B1 (chromosome 7) and HNRNPA1 (chromosome 12) genes account for some families with IBMPFD. 5 We first raised the possibility of a connection between IBMPFD and amyotrophic lateral sclerosis (ALS) after mutations in the VCP gene were identified in patients with familial ALS.…”
mentioning
confidence: 99%